A facile green approach for fabricating bacterial cellulose scaffold with macroporous structure and cell affinity. (November 2019) - Zhong, Meiling; Li, Jinsheng; Tang, Aoqi; Zhang, Qi; Ji, Dehui; Peng, Mengxia; Zhang, Richao; Xiong, Guangyao; Wan, Yizao; Fan, Hongsong
Bacterial cellulose holds great promise for tissue engineering, but its application is greatly limited due to the lack of large pores and poor cell affinity. In this study, macroporous bacterial cellulose was fabricated through the dissolution of gelatin microspheres, which were incorporated with bacterial cellulose during bacterial cellulose fabrication. Then, gelatin was immobilized onto bacterial cellulose surface via procyanidins crosslinking. The results confirmed that the scaffolds possessed interconnected macroporous structure, high porosity, good water uptake ability, and good mechanical properties. The results of evaluation of cells showed that cells migrated to the inner of macroporous affinitive bacterial cellulose and displayed better spreading as well as proliferation than that on pure bacterial cellulose surfaces. The macroporous affinitive bacterial cellulose show potential as a scaffold for tissue engineering.